Unspanned Global Macro Risks in Bond Returns - Zhao, Feng; Zhou, Guofu; Zhu, Xiaoneng (Management Science, 2021)
We examine the macro-spanning hypothesis for bond returns in international markets. Based on a large panel of real-time macroeconomic variables that are not subject to revisions, we find that global macro factors have predictive power for bond returns unspanned by yield factors. Furthermore, we estimate macro-finance term structure models with the unspanned global macro factors and find that the global macro factors influence the market prices of level and slope risks and induce comovements in forward term premia in global bond markets. This paper was accepted by David Simchi-Levi, finance.